2012
DOI: 10.1021/ic3008393
|View full text |Cite
|
Sign up to set email alerts
|

Phosphopeptide Selective Coordination Complexes as Promising Src Homology 2 Domain Mimetics

Abstract: Src Homology 2 (SH2) domains are the paradigm of phosphotyrosine (pY) protein recognition modules and mediate numerous cancer-promoting protein-protein complexes. Effective SH2 domain mimicry with pY-binding coordination complexes offers a promising route to new and selective disruptors of pY-mediated protein-protein interactions. We herein report the synthesis and in vitro characterization of a library of coordination complex SH2 domain proteomimetics. Compounds were designed to interact with phosphopeptides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…To assess the receptor affinity towards peptide sequences, a 5-carboxyuorescein (FAM) uorescent label was appended through a glycine linker at the N-terminus of the target peptide sequences and binding constants (K a , Table S1, ESI †) were determined by a high throughput uorescence intensity (FI) assay previously described. 12 The binding affinities determined by FI assay are in close agreement with the values obtained by analogous isothermal titration calorimetry (ITC) binding experiments (Fig. 3, Table 1).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…To assess the receptor affinity towards peptide sequences, a 5-carboxyuorescein (FAM) uorescent label was appended through a glycine linker at the N-terminus of the target peptide sequences and binding constants (K a , Table S1, ESI †) were determined by a high throughput uorescence intensity (FI) assay previously described. 12 The binding affinities determined by FI assay are in close agreement with the values obtained by analogous isothermal titration calorimetry (ITC) binding experiments (Fig. 3, Table 1).…”
supporting
confidence: 83%
“…Notably, it was demonstrated that such systems could effectively sense hyper-phosphorylated Tau peptides present in Alzheimer's samples 10 and disrupt the association between a CTD and WW domain. 11 However, only few studies 12,13,14 have tried to address whether (Zn 2+ ) 2 -BDPA receptors can selectively bind to clinically relevant mono-phosphorylated peptide sequences. We herein describe the development of novel bivalent receptors for delineating the structural facets required for selective recognition of mono-phosphoserine containing peptides and for more generally assessing the likelihood of identifying therapeutically viable phosphopeptide-selective binders.…”
mentioning
confidence: 99%
“…88 Building on Hamachi G used bis(Cu(II)Dpa) and bis(Zn(II)Dpa) complexes to bind to phosphotyrosine on signal transduction and activator of transcription 3 (STAT3), thus inhibiting STAT3/STAT3 dimerisation. 89,90 ITC and fluorescence polarisation (FP) data demonstrated the copper(II) complexes bound to a phosphopeptide (with micromolar Kd), thus inhibiting the phosphopeptide-protein complex, with micromolar Ki. 89 The copper(II) complexes were further shown to inhibit STAT3/STAT3:DNA binding in an electrophoretic mobility shift assay (EMSA) with IC50 = 8.2 M. They also exhibited low micromolar IC50s in 3 different cancer cell lines but much lower inhibition, and low cytotoxicity, in healthy NIH3T3 cells, thus highlighting their potential therapeutic utility.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…90 Several of these compounds were also shown to be cytotoxic in three types of cancer cell. 90 Co-ordination complexes as ligands for protein surfaces Several surface mimetics use metals as a core structural unit, while the ligands surrounding the metal are used for protein binding. Using metals in a purely structural capacity, especially in thermodynamically or kinetically inert compounds, allows for their use in cellulo, as the metal is unable to non-specifically coordinate to biomacromolec ule s and exert a toxic effect.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…33,34 The molecular design concept of modified scaffolds has been used before to enhance binding affinity of Zn-BDPA structures to small, water-soluble phosphorylated target molecules such as inorganic phosphate, 3538 nucleoside polyphosphates, 39 and phosphorylated peptides. 4042 However, there is no reported attempt to improve Zn-BDPA recognition of PS buried in a bilayer membrane. The strategy of designing modified Zn-BDPA scaffolds de novo using computer modeling was judged to be unreliable given the structural flexibility of the Zn-BDPA scaffold and the dynamic, amphiphilic properties of a target PS-rich bilayer membrane.…”
Section: Introductionmentioning
confidence: 99%